First record of the ant cricket Myrmecophilus (Myrmecophilina) americanus (Orthoptera: Myrmecophilidae) in Mexico - Ortega-Morales, Aldo I.; Rodríguez, Quetzaly K. Siller; Garza-Hernández, Javier A.; Adeniran, Adebiyi A.; Hernández-Triana, Luis M.; Rodríguez-Pérez, Mario A. (Zootaxa, 2017)
In September 2004, the New World ant cricket, Myrmecophilus americanus Saussure, 1877, was collected in association with longhorn crazy ants, Paratrechina longicornis (Latreille. 1802), in the state of Coahuila, Mexico. We are reporting the DNA barcode using the mitochrondrial cytochrome oxidase subunit I for this first record of M. americanus in Mexico.